SOLUSI POLINOMIAL PERSAMAAN INTEGRO-DIFERENSIAL FREDHOLM LINEAR DENGAN KOEFISIEN KONSTAN - Taufik, Imam; ', Syamsudhuha; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This paper discusses how to obtain a polynomial solution of linear Fredhlom integrodifferential equation with constant coefficients using a matrix method. The Linear Fredhlom integro-differential equation with constant coefficients and its initialboundary conditions are tranformed into a matrix, resulting a system of linear equations. Polynomial solutions of linear Fredhlom integro-differential is obtained by solving the system of linear equations.